Microstructural Characteristics of Modified ODS Ni-Based Superalloys Fabricated using Laser-Powder Bed Fusion - Dong Wan Lee; Jin Woo Kim; Su Gwan Lee; Dhin Van Cong; Jin Chun Kim; Hwi Jun Kim; Joong Gyeong Lim; Tae Sik Yoon (Archives of Metallurgy and Materials)
Oxide dispersion-strengthened (ODS) superalloys are usually manufactured by a hot isostatic pressing after mechanical alloying (MA-HIP). However, this process cannot produce complex-shaped parts. Here, we used an additive manufacturing product (powders produced by laser powder bed fusion, L-PBF) to address this issue. Modified ODS Ni-based superalloy powders with a similar composition to the mechanical alloy 6000 (MA6000) were manufactured using a gas atomization process. The obtained powders and L-PBF synthesized samples were analyzed by scanning electron microscopy (SEM), X-ray diffraction (XRD), LPSA, and EBSD analyses.